Hydroxyapatite From the Skull of Tuna (Thunnus obesus) Head Combined With Chitosan to Restore Locomotive Function After Spinal Cord Injury - Ma, Chen-chen; Wang, Xi-chang; Tao, Ning-ping (Frontiers in Nutrition, 2021)
Hydroxyapatite is an important calcium in the head of tuna and widely used to repair bone defects. Chitosan is a degradable basic polysaccharide with good biocompatibility. To evaluate the effect of chitosan modified hydroxyapatite (chitosan-hydroxyapatite) nanoparticles in the repair of rat spinal cord injury (SCI), we successfully prepared chitosan-hydroxyapatite nanoparticles. The results revealed that the chitosan-hydroxyapatite particles could remain stable at low temperature for a long time, and chitosan-hydroxyapatite treatment significantly improved SCI, while chitosan treatment resulted in no significant increase of the Basso Beattie Bresnahan (BBB) scores compared with the control group. In addition, chitosan-hydroxyapatite nanoparticles also significantly reduced the lesion cavity volume and improved the dispersed structure, indicating it could promote the recovery of tissue function of SCI rats. This study explored the therapeutic effect of chitosan-hydroxyapatite nanoparticles on the rat SCI, providing experimental evidence for further research on its application in spinal cord repair, and the study also played an important role in promoting the effective utilization of tuna head.